Performance of soybean cultivars in three sowing dates in Rio Grande do Sul, Brazil - Rizzo Bonato, Emídio; Fernando Bertagnolli, Paulo; Carlos Ignaczak, João; Luiz Tragnago, José; de Assis Librelotto Rubin, Sérgio (Pesquisa Agropecuaria Brasileira, 1998)
Aiming to assess the behavior of soybean cultivars (Glycine max L. Merril) recommended for the State of Rio Grande do Sul, Brazil, at different sown dates, three experiments were carried out during three years, at four sites, with sowings in mid-October, mid-November, and mid-December. A complete randomized block design with split plots was used. The yield of the cultivars sown in mid-December was lower than the yields obtained in the remaining dates for the three cycles. Sowing in mid-October and mid-November resulted in yields that were similar for the group of early and late cultivars, while the yield from mid-November sowing date was higher than mid-October for intermediate cycle cultivars. The performance of cultivars of all three cycles was similar at a given sowing date. Average reduction in yield from plots sown in December, as compared to November, was as follows: 17.3% for early cultivars; 17.1% for intermediate cycle cultivars; and 19.7% for late cultivars. A similar behavior was observed for grain size, plant height, and the insertion of lower pods. It is concluded that there is a possibility of sowing presently grown early cultivars from mid-October onwards and also that the cultivars of all three cycles show a similar yield potential in mid-December sowings.